A Adaptation and translation of the Psy-Flex in university students in Lima Metropolitana - Arroyo Pizarro, Pedro Luis; Peña-Muñante, Gonzalo; Osorio Chipana, Margot; Moreno-Montero, Esteban (Medicina Clínica y Social, 2025)
Introduction: The PsyFlex is a relevant measure for clinical practice given that it facilitates therapeutic planning and represents a measure of change in intervention sessions; however, it is not adapted to the Peruvian context. Objective: To adapt and translate the Psy-Flex in a sample of Peruvian university students. Methodology: Two samples of 273 participants, each aged 18 to 59 years of both sexes, were used. Results: Absolute (RMSEA=.000 to .074; SRMR=.014 to .031) and relative (CFI=.977 to 1.000; TLI=.962 to 1.005) optimal fit indices and reliability indices above .85 for the one-factor structure were identified, thus, the instrument has optimal evidence of validity and reliability. Discussion: The findings are partially consistent with other studies due to morpho-syntactic characteristics of the translation process from English to Spanish, reflecting the unidimensional nature of the test.
Keywords: Psychometrics; Acceptance and Commitment Therapy; Clinical Psychology; Perú; Students